Effects of Government Assistance Programs on the Well-being of Urban Low-income Households During Covid-19 Pandemic in Malaysia - Mohd Azlan Shah Zaidi; Md Shafiin Shukor; Zurina Kefeli@ Zulkefli; Aainaa Amirah Haron; Ros Amira Mohd Sudin (Asian Economic and Social Society (AESS), 2024)
Indexed by Scopus